Revision of the taxonomic status of Lysidice (Polychaeta, Eunicidae) in the Western Caribbean Sea with observation on species reproductive features and habitat preference - Carrera-Parra, L.F.; Fauchald, K.; Gambi, M.C. (Italian Journal of Zoology, 2011)
Although most of the Eunicidae (Polychaeta) of the Western Caribbean Sea appear to be well studied, the taxonomic status of Lysidice has yet to be evaluated. A first attempt to revise the taxonomy of this genus is here presented, based on material collected at Carrie Bow Cay (CBC, Belize), as well as at other sites along the Yucatan Peninsula, representing a variety of habitat types (coralline rock–coral rubbles, sponges, coralline sands, Thalassia testudinum meadows) and depths (0.5–20 m). The collected new taxa found were described and compared with literature description of other known species, as well as with museum specimens of the type-species of the genus, Lysidice ninetta Audouin & Milne Edwards, which has been confused with and synonymized with many Caribbean morphotypes of Lysidice. The analysis reveals the presence of five previously undescribed species of Lysidice: L. caribensis n. sp. and L. adrianae n. sp., preferentially associated with coralline rock; L. thalassicola n. sp. associated with Thalassia testudinum meadows, as a borer in the seagrass sheaths, and representing the only polychaete species strictly associated with Thalassia; lastly, L. carriebowensis n. sp. and L. phyllisae n. sp. are less common and collected only at CBC in association with coralline rock (coral rubble). Several specimens of the three more common new species, L. caribensis, L. thalassicola and L. adrianae were found mature, both males and females, with an epitokous transformation in which nearly two-thirds of the body is swollen and full of gametes, and with eyes extraordinarily enlarged. The ultrastrucure analysis of mature spermatozoa of L. caribensis and L. adrianae shows a typical ect-aquasperm structure. These show that Lysidice is a highly diversified genus in the Western Caribbean, with the different species showing clear habitat and geographic separation. [Proceedings of the 10th International Polychaete Conference (20-26 June 2010, Lecce, Italy) ]
World Polychaeta Database (WPolyDb)